Implementation of “Ngerti, Ngrasa, Nglakoni” in The Leadership of Sono Hamlet Youth Organization - Jamaluddin, Akmal; Nurjana, Anisa; Noperian, Jogi; Dewi, Esta Lestariana; Putrisia, Ezdwima; Kusumawardhani, Ratih (IJCS: International Journal of Community Service, 2024)
The main objective of this program is to provide provision and guidance that operates in the social and environmental fields with the main focus on the development of young people. Community Service was carried out on October 15 2024 in Sono Hamlet, Kretek District, Bantul Regency. This Community Service ran smoothly and was attended by 11 young people out of 15 invited people. The material presented is related to the concept of student gardens, namely Tri Nga "Understanding, Ngrasa, and Nglakoni" which is certainly relevant to the needs of young people, most of whom face problems related to consistency and discipline in participating in social activities in the community. During the activity, the young people were very enthusiastic in participating in the coaching activity until the end. The young people hope that this community service activity will be carried out regularly. The coaching results show that young women are more disciplined than young people in participating in activities.